Struktur Pelatihan Yoga Ä€sanas Bagi Anak-Anak, Remaja Dan Dewasa Di Sanggar Samirata - Juniartha, Made G.; Sugata, I Made; Dwitayasa, I Made; Wika, I Made; Piartha, I Nyoman (JURNAL YOGA DAN KESEHATAN, 2021)
Yoga is a way to connect or unite in the spiritual or spiritual dimension which is the main process / path to achieve the goal, namely eternal freedom or the union of the soul with God. This oneness exists after breaking the duality of mind into the highest consciousness. Ä€sanas is the third part of the eight yoga paths, which are known as astÄngga yoga or the eight sections of yoga. The aim is to make our bodies steady and ready for higher techniques such as pranayama (breath control), pratyahara (sense withdrawal), dharana (concentration), dhyana (meditation) and Samadhi (cosmic realization). The method used in this writing uses qualitative methods, using qualitative descriptive analysis. Besides that, in the implementation of the training, the method of material presentation, question and answer method, and practical method is also carried out. Data collection used by using observation, interview and documentation techniques. Through Äsanas yoga training which is not theoretical but direct practice through the Äsanas yoga training structure by emphasizing the importance of deep understanding of the philosophy of each Äsanas pose that is carried out. So that by staying more persistent, it will be easier to concentrate and meditate. In addition, the Äsanas movement balances the production of hormones from the various glands, the stretching and bending position of the Äsanas movement, which is carried out for a certain period of time, puts special and sustained pressure on the glands so that it stimulates the glands in various ways, regulates glandular production and ultimately going to control emotions. If the deficiency of the glands is resolved, the mind becomes free from emotional distress and a perfect inner calm will be achieved. So that the training participants will feel the benefits both morally, physically, mentally and spiritually by making the practice of yoga as a sadhana.